TANAM 1000 POHON MAHONI WADUK DURIANGKANG KOTA BATAM - Haposan Banjarnahor; Mortigor Afrizal Purba (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2025)
BP Batam, together with the Banjarnahor Family of Batam City, planted 1000 mahogany trees located in the Water Catchment Area of the Duriangkang Reservoir, Batam City. The development of Batam City as an industrial area must be balanced with sustainable greening to maintain water discharge for the needs of the Batam City community. Batam City's water catchment consists of seven reservoirs that serve as raw water sources for the city, namely: Sei Ladi Reservoir, Sei Harapan Reservoir, Muka Kuning Reservoir, Tembesi Reservoir, Mongak Reservoir, Nongsa Reservoir, and Duriangkang Reservoir. Seeing the increasingly high population growth of Batam City, BP Batam and the Banjarnahor Family jointly carried out a collaborative action to plant 1000 Mahogany trees in the DTA (Water Catchment Area) of the Duriangkang Reservoir. This collaborative tree-planting action by BP Batam and the Banjarnahor Family was also supported by the Sei Jang Duriangkang River Flow Management Center and involved 100 volunteers from the Banjarnahor Family along with BP Batam employees.